Recent Discoveries in Zingiberaceae: A Review Highlighting New Species from Asia Over the Last Six Years - Afifudin, Alfin Fatwa; Aina, Avivi Nur; Arneni, Wanda Dya; Clement, Christopher; Wijaya, Nabila Hapsari; Dewi, Firli Rahmah Primula; Irawan, Bambang (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
The increasing pace of habitat loss and environmental changes necessitates urgent research into the biodiversity of plant families such as Zingiberaceae. This review explores the discovery of new species within the Zingiberaceae family in Asia over the past six years, focusing on their distribution, characteristics, and the significance of these findings. The literature review involved searching various databases, including ScienceDirect, Scopus, Web of Science, Google Scholar, Google Books, and the Internet Archive, for references on new Zingiberaceae species. Specific search terms such as "new Zingiberaceae species," "discovery," "Asia," and "characterization" were used to identify pertinent articles. After collecting and analysing data, a total of 119 new species were identified across 11 countries, namely Cambodia, China, India, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Taiwan, Thailand, and Vietnam. The genera include Alpinia, Boesenbegia, Curcuma, Etlingera, Globba, Hedychium, Kaempferia, Monolophus, Plagiostachys, Pleuranthodium, Sundamomum, Wurfbaiana, Conamomum, and Zingiber. Notably, the genus Curcuma was the most prolific, with 37 new species. Thailand emerged as the leading country in terms of new species discoveries. This comprehensive review highlights the diverse characteristics of these species and underscores the critical role of Zingiberaceae in ecological and economic contexts. The findings emphasize the importance of continued botanical exploration and research to enhance our understanding of biodiversity and to unlock potential applications in medicine, agriculture, and other industries.